Comparison of two doses of breast milk and sucrose during neonatal heel prick - (:unkn) unknown (WILEY-BLACKWELL PUBLISHING, INC, 2010)
Background: The aim of the present study was to test analgesic effects of double- versus single-dose breast milk and compare this effect with efficacy of double- versus single-dose sucrose in a group of healthy term newborns during heel prick blood sampling. Methods: Healthy newborns (n = 142) were consecutively allocated to one of the six groups: group 1, single-dose breast milk; group 2, single-dose sterile water; group 3, single-dose 12.5% sucrose; group 4, two doses breast milk; group 5, two doses sterile water; and group 6, two doses 12.5% sucrose before the heel prick. The medians for crying time and the pain scores according to the neonatal facial coding system were recorded. Results: Crying times were 117 s, 126 s, 82 s, 128 s, 117 s, and 95 s in groups 1-6, respectively (P = 0.053). The mean pain scores were 4.60, 5.82, 3.91, 4.94, 5, and 4.05 in groups 1-6, respectively (P = 0.068). There was a significant difference between the groups for mean pain scores at 1 min and 3 min. There was a significant difference between the single-dose sucrose group and single-dose sterile water group at 1 min (P = 0.002). The babies in the sucrose group were active awake, whereas the ones in the breast milk group were asleep before heel prick. Conclusion: Two doses of sucrose solution were not superior to single-dose sucrose. Neither single nor double doses of breast milk were effective in relieving pain in neonates. Two milliliters breast milk does not reduce response to pain during minor painful procedures in term neonates even when two doses have been given. Further studies are needed.
Keywords: breast milk; neonatal pain; surose; 10-DAY-OLD RATS; PROCEDURAL PAIN; INDUCED ANALGESIA; NEWBORN-INFANTS; HYPOALGESIA; EXPRESSION; MEDIATION; CRY